Teaching Speaking with Multiple Intelligences Method for Eleventh Grade Students of SMKN 3 Langsa - Kausar , Cut Intan; Swastica , Nabilla Aulia; Santoso, Anggun; Tahani , Haura; Rizky, Indah Nur (JL3T (Journal of Linguistics, Literature and Language Teaching), 2020)
The research authorized “Teaching Speaking with Multiple Intelligences Method” focus on observing the influence of application of Multiple Intelligences Method for affecting students’ speaking skill. The purpose of this study was the application of Multiple Intelligences which was dominant in teaching speaking. This study used experimental method with quasi- experimental as the design toward the students. There were two groups consisted of experimental and control group. The experimental group was taught by implementing Multiple Intelligence method and the control group was taught by using usual technique of the teacher. The data were obtained through pre-test and post-test with T-test computation to analyze it. The research states that the implementation of Multiple Intelligences method was more effective in affect students’ speaking skill. It was proven by the result of statistical computation which uttered that t-value (18.54) was higher than t-table, t-value > t-table, (2.000, α = 0.05 and dk = 58). In conclusion, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted